T63. Repercussions of the genomic medicine narrative in psychiatry on beliefs, clinical practices and public policy in Costa Rica: a qualitative study - Raventós Vorst, Henriette (2022)
Costa Rica, as a small middle-income country with a universal public health care system experiencing economic pressures by changing demographics, high migration from neighboring countries, budget restrictions, and enormous expenses due to the pandemic, the pressure to incorporate unproven genomic technoscientific developments by different social actors including the general population, could put at risk the stability of our health care system. The goal of this project was to explore and analyze the presence and possible impact of the genomic medicine narrative on the beliefs, clinical practices, and public policies in Costa Rica for major mental disorders, as a case study on the social impacts of genomics or genetization, as has been named by Hedgecoe.